Radiation-induced DNA damage and repair in lymphocytes from breast cancer patients and their correlation with acute skin reactions to radiotherapy - Popanda, Odilia; Ebbeler, Reinhard; Twardella, Dorothee; Helmbold, Irmgard; Gotzes, Florian; Schmezer, Peter; Thielmann, Heinz Walter; Fournier, Dietrich von; Haase, Wulf; Sautter-Bihl, Marie Luise; Wenz, Frederik; Bartsch, Helmut; et al. (International journal of radiation oncology, biology, physics, 2003)
Purpose - Repair of radiation-induced DNA damage plays a critical role for both the susceptibility of patients to side effects after radiotherapy and their subsequent cancer risk. The study objective was to evaluate whether DNA repair data determined in vitro are correlated with the occurrence of acute side effects during radiotherapy. - Methods and materials - Breast cancer patients receiving radiation therapy after a breast-conserving surgery were recruited in a prospective epidemiologic study. As an indicator for clinical radiosensitivity, adverse reactions of the skin were recorded. Cryo-preserved lymphocytes from 113 study participants were γ-irradiated with 5 Gy in vitro and analyzed using the alkaline comet assay. Reproducibility of the assay was determined by repeated analysis (n = 26) of cells from a healthy donor. A coefficient of variation of 0.3 was calculated. - Results - The various parameters determined to characterize the individual DNA repair capacity showed large differences between patients. Eleven patients were identified with considerably enhanced DNA damage induction, and 7 patients exhibited severely reduced DNA repair capacity after 15 and 30 min. Six patients were considered as clinically radiosensitive, indicated by moist desquamation of the skin after a total radiation dose of about 50 Gy. - Conclusions - Using the alkaline comet assay as described here, breast cancer patients were identified showing abnormal cellular radiation effects, but this repair deficiency corresponded only at a very limited extent to the acute radiation sensitivity of the skin. Because impaired DNA repair could be involved in the development of late irradiation effects, individuals exhibiting severely reduced DNA repair capacity should be followed for the development of late clinical symptoms.